A political arena or a chambre de réflexion? An examination of the reflective role of Dutch senators. Issue 4 (1st October 2020) - Otjes, Simon
ABSTRACT: Senators are expected to perform a reflective role: they are not supposed to simply look at the policy content of the legislation but also at its technical aspects and its constitutionality; moreover, they are expected to be more independent from the division between government and their own party. This article examines voting behaviour in the Dutch senate between 2000 and 2015 to determine to what extent this is the case. It finds that there are only small differences in the voting of senators and members of the house that can be explained by the reflective role of senators.